COMPARISON OF THE EFFECTIVENESS OF BUILDING INFORMATION MODELING BASED COST ESTIMATION AGAINST THE CONTRACTOR'S COST BUDGET PLAN IN DEVELOPMENT PROJECT OF BANJARBARU BAUNTUNG MARKET - Muhammad Hanugrah Adipratama; Husnul Khatimi (CERUCUK, 2022)
This study focuses on the use of Building Information Modeling (BIM) which begins with creating a 3D digital model (virtual building) which serves as a means for planning, designing, implementing development, and maintaining the building and its infrastructure for all parties involved in the project. Unlike other studies that use concrete structures, this study refers to the Bauntung Banjarbaru Market building with a steel structure. BIM software program is specific and correct. Specific is within the use of BIM information is taken and adapted to real conditions within the area. Correct is a constructible model, that is, the model that is created is the same as the model that was constructed. Besides, when there is a change in the model, the resulting cost estimate can change automatically.Modeling of building structures includes modeling of reinforced concrete structures and steel structures. The modeling is done using a software called Tekla Structures with a South-East Asia environment that refers to the plan drawing. After the modeling is complete, the work unit price is inputted into the software. The output of this modeling is direct cost estimation for structural work. For manual cost estimation using cost budget plan that has been obtained from the contractor in the form of a Microsoft Excel file.From the results of the analysis of the two cost estimates, the resulting comparison of the cost difference is quite scanty. The difference between manual cost estimation and BIM based cost estimation is 0.26%. So, it can be concluded that the use of BIM based cost estimation can be used because it produces cost estimates that are faster than using manual calculations made by contractors.The use of BIM can reduce costs and inaccuracies in the calculation of estimates in projects because it can be done more thoroughly. Keywords: BIM-based cost estimation, Tekla Structures, building structures